Seasonal variations and the COVID-19 pandemic: impact on antimicrobial stewardship and antibiotic prescribing in a UK secondary care setting to combat antimicrobial resistance—a pilot study - Abdelsalam-Elshenawy, Rasha; Umaru, Nkiruka; Aslanpour, Zoe (Frontiers in Microbiology, 2025)
Antimicrobial resistance (AMR) remains a significant global health challenge, exacerbated by inappropriate antibiotic use, particularly during crises such as the COVID-19 pandemic. This pilot study evaluates the impact of seasonal variations and the pandemic on antimicrobial stewardship (AMS) practices in a UK secondary care setting. Using an interrupted time-series analysis, the study examined antibiotic prescribing patterns for respiratory tract infections (RTIs) during the pre-pandemic period of 2019 and the pandemic year of 2020. Among the 80 admissions reviewed, communityacquired pneumonia (CAP) was the most frequent diagnosis, with cases peaking at 15 in December 2019, illustrating the seasonal burden of RTIs. AMS interventions were assessed using the CARES framework, as recommended by the United Kingdom Health Security Agency’s (UKHSA) Start Smart, Then Focus toolkit. This CARES framework consists of five key actions: Cease, which involves discontinuing antibiotics if no infection is present; Amend, modifying antibiotic therapy based on clinical response or diagnostic findings; Refer, consulting specialised services when additional expertise is required; Extend, continuing antibiotic therapy with a documented review date; and Switch, transitioning from intravenous to oral antibiotic therapy when clinically appropriate. Notable shifts in AMS practices were observed, with Cease interventions increasing from 5% in winter 2019 to 9% by early spring 2020, Amend actions briefly spiking in March 2020, and Switch interventions peaking at 6% in spring 2020, reflecting dynamic stewardship responses to the evolving pandemic landscape. While the small sample size limits statistical power, a more extensive validation sample would strengthen the robustness of the data extraction tool and enhance its credibility for broader applications. Nevertheless, these findings highlight the importance of adaptive, sustainable, and resilient AMS strategies that align with seasonal trends to mitigate AMR risks and ensure effective healthcare delivery during public health emergencies. The study highlights the value of pilot testing in ensuring feasibility and reliability, advocating for the development of robust AMS frameworks to combat AMR and build healthcare resilience during future global crises.